Textbbook on Agricultural Communication - Sandhu A.S.; Sandhu A.S. (NEW Delhi Oxford & IBH, 2010)
the book introduces several new concepts such as communication competence ,communication effectiveness,communication intelegence
communication communicator message radio television
Keywords: communication, communicator ,message ,radio,television